Transmural Autonomic Regulation of Cardiac Contractility at the Intact Heart Level - Aguilar-Sanchez, Yuriana; Rodriguez de Yurre, Ainhoa; Argenziano, Mariana; Escobar, Ariel L.; Ramos-Franco, Josefina (Frontiers in Physiology, 2019)
The relationship between cardiac excitability and contractility depends on when Ca2+ influx occurs during the ventricular action potential (AP). In mammals, it is accepted that Ca2+ influx through the L-type Ca2+ channels occurs during AP phase 2. However, in murine models, experimental evidence shows Ca2+ influx takes place during phase 1. Interestingly, Ca2+ influx that activates contraction is highly regulated by the autonomic nervous system. Indeed, autonomic regulation exerts multiple effects on Ca2+ handling and cardiac electrophysiology. In this paper, we explore autonomic regulation in endocardial and epicardial layers of intact beating mice hearts to evaluate their role on cardiac excitability and contractility. We hypothesize that in mouse cardiac ventricles the influx of Ca2+ that triggers excitation-contraction coupling (ECC) does not occur during phase 2. Using pulsed local field fluorescence microscopy and loose patch photolysis, we show sympathetic stimulation by isoproterenol increased the amplitude of Ca2+ transients in both layers. This increase in contractility was driven by an increase in amplitude and duration of the L-type Ca2+ current during phase 1. Interestingly, the β-adrenergic increase of Ca2+ influx slowed the repolarization of phase 1, suggesting a competition between Ca2+ and K+ currents during this phase. In addition, cAMP activated L-type Ca2+ currents before the Ca2+ release activated the Na+-Ca2+ exchanger currents, indicating Cav1.2 channels are the initial target of PKA phosphorylation. In contrast, parasympathetic stimulation by carbachol did not have a substantial effect on amplitude and kinetics of endocardial and epicardial Ca2+ transients. However, carbachol transiently decreased the duration of the AP late phase 2 repolarization. The carbachol-induced shortening of phase 2 did not have a considerable effect on ventricular pressure and systolic Ca2+ dynamics. Interestingly, blockade of muscarinic receptors by atropine prolonged the duration of phase 2 indicating that, in isolated hearts, there is an intrinsic release of acetylcholine. In addition, the acceleration of repolarization induced by carbachol was blocked by the acetylcholine-mediated K+ current inhibition. Our results revealed the transmural ramifications of autonomic regulation in intact mice hearts and support our hypothesis that Ca2+ influx that triggers ECC occurs in AP phase 1 and not in phase 2.